A programmable tunable active grounded and floating immittance circuit using CCTA and their applications. Issue 1 (2nd January 2023) - Kumar, Navnit; Kumar, Manjeet; Pandey, Neeta
ABSTRACT: This article presents a novel grounded and floating immittance circuit. It can simulate any one of the floating and grounded positive and negative inductor circuit, positive and negative capacitor circuit, and positive and negative resistor circuit. The novelty of the proposed circuit is its capability to provide positive and negative immittances without any change of passive component and matching condition. In addition, active realisations of positive and negative fractional order immittance circuits are presented. Thus, this paper presents 16 types of immittances which cover entire two-dimensional phase plane. Grounded immittance circuit uses one active block Current Conveyor Transconductance Amplifier (CCTA), one grounded MOS resistor and one grounded passive component while floating immittance circuit employs two CCTAs and three components. The immittance of the proposed circuits can be tuned by changing the bias current of CCTA and bias voltage of MOS resistor. The frequency responses of the proposed circuits are verified using SPICE simulation based on the 0.18 µm TSMC CMOS technology parameter. The performance of the proposed positive immittance circuits is demonstrated by active filter design using SPICE in conjunction with MATLAB. The performance of the proposed negative immittance circuit is demonstrated through inductance cancellation.